Transparansi Akuntabilitas Realisasi Anggaran Publik Berdasarkan Prinsip Islam dalam Mencegah Praktik Korupsi (Studi Pada Dinas Pekerjaan Umum Kabupaten Takalar) - Bakhtiar, Nursinta; Suwandi, Memen; Rahma Sari, Nur (Income Journal: Accounting, Management and Economic Research, 2023)
This study aims to determine the use of Public Budget Realization in the Takalar district public works office, to determine the transparency and accountability system for the use of public budget realization and to determine the application of Islamic principles namely shiddiq, amanah, tabliq and fathonah in the Takalar district public works office. The method according to this research is a qualitative research method. In this study used a type of qualitative research based on an analytical descriptive approach and the data used by researchers in this study were primary and secondary data. By using data source triangulation to test the validity of the data obtained. The results of this study indicate that the process of managing public budgets at the planning, implementation and accountability stages has been prepared according to systems and procedures. Transparency and accountability provide information openly and honestly to the public, taking into account the public's right to a comprehensive understanding of budget management responsibilities. One of the benefits of applying the principles of transparency and accountability is preventing corrupt practices. Based on Islamic principles by applying the characteristics of the Prophet and Messenger, namely: shidiq, amanah, tabligh, and fathonah in leadership to uphold morality, maintain trust, be firm in your convictions, honest in carrying out the duties and responsibilities assigned to them, strong in faith in rejecting temptations and opportunities to stray. So the level of trust is greater.